Motivating nonexporters to go abroad: Investigating the role of government using evidence from a developing country - Paul Jones (Strategic Change, 2018)
Government export promotion programs enhance export intention of small and medium enterprises through boosting their managerial and relational resources. In Algeria, managerial and relational resources are the main drivers of export intention, whereas organizational capabilities have a limited influence. Export promotion programs increase firms’ managerial, organizational and relational resources. At the pre‐export stage, informational programs are more likely to enhance SMEs’ export initiation than experiential ones.